Advancements in energy storage applications: harnessing the potential of fish industry waste - Vishal Rajput; Bindu Naik; Vijay Kumar; Vivek Kumar; Saurav Chandra Bhatt; Sarvesh Rustagi (Discover Materials)
Abstract This review paper provides a comprehensive overview of recent advancements in energy storage applications, focusing on the utilization of fish industry waste as a sustainable resource. The paper is structured into several key sections, each highlighting a different aspect of this emerging field. Firstly, it explores the use of nanoporous carbons for high-density lithium-ion battery (LIB) anodes, discussing their potential to enhance energy storage capabilities. Secondly, it examines the development of advanced LIB anodes from fish waste-derived nanostructures, showcasing novel approaches to material synthesis. Additionally, the paper delves into the utilization of biomass-derived carbons for sodium-ion battery (NIB) anodes, presenting insights into their role in advancing energy storage technology. Furthermore, it discusses the integration of biomass-derived porous carbons to improve the performance of lithium-sulfur batteries, highlighting strategies to overcome existing limitations. Moreover, the paper explores the application of biomass-derived carbon materials in supercapacitors, emphasizing their potential for high-performance energy storage solutions. Lastly, a significant focus is placed on protein batteries, a novel concept that utilizes seafood waste as a sustainable source for energy storage. The paper elaborates on the processes involved in transforming fish waste into suitable materials for battery electrodes and evaluates the performance of these protein batteries in terms of efficiency, stability, and capacity. Through a structured analysis of recent advancements, this review underscores the potential of biomass-derived materials in addressing sustainability challenges while advancing energy storage technology. Graphical abstract